St. John's French Church, West Warwick, R.I (68993) - Tichnor Quality (Wikimedia Commons, 1930)
Notice image issue de Wikimedia Commons. Titre: St. John's French Church, West Warwick, R.I (68993). Title: St. John's French Church, West Warwick, R.I. Subjects: Churches Places: Rhode Island > Kent (county) > West Warwick Notes: Title from item. Extent: 1 print (postcard): linen texture, color | 5 1/2 x 3 1/2 in. Accession #: 06_10_002107
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; architecture; Histoire Locale; église; Carte postale